Monitoring CML patients responding to treatment with tyrosine kinase inhibitors: review and recommendations for harmonizing current methodology for detecting BCR-ABL transcripts and kinase domain mutations and for expressing results - Hughes, Timothy P.; Deininger, Michael; Hochhaus, Andreas; Branford, Susan; Radich, Jerald; Kaeda, Jaspal; Baccarani, Michele; Cortes, Jorge; Cross, Nicholas C. P.; Druker, Brian J.; Gabert, Jean; Grimwade, David; et al. (Blood, 2006)
The introduction in 1998 of imatinib mesylate (IM) revolutionized management of patients with chronic myeloid leukemia (CML) and the second generation of tyrosine kinase inhibitors may prove superior to IM. Real-time quantitative polymerase chain reaction (RQ-PCR) provides an accurate measure of the total leukemiacell mass and the degree to which BCR-ABL transcripts are reduced by therapy correlates with progression-free survival. Because a rising level of BCR-ABL is an early indication of loss of response and thus the need to reassess therapeutic strategy, regular molecular monitoring of individual patients is clearly desirable. Here we summarize the results of a consensus meeting that took place at the National Institutes of Health (NIH) in Bethesda in October 2005. We make suggestions for (1) harmonizing the differing methodologies for measuring BCR-ABL transcripts in patients with CML undergoing treatment and using a conversion factor whereby individual laboratories can express BCR-ABL transcript levels on an internationally agreed scale; (2) using serial RQ-PCR results rather than bone marrow cytogenetics or fluorescence in situ hybridization (FISH) for the BCR-ABL gene to monitor individual patients responding to treatment; and (3) detecting and reporting Philadelphia (Ph) chromosome-positive subpopulations bearing BCR-ABL kinase domain mutations. We recognize that our recommendations are provisional and will require revision as new evidence emerges. (Blood. 2006;108:28-37)
Gesehen am 10.05.2022